Consumer Attitudes Toward Web Personalization: A Malaysian Perspective - Milin, Rondy M. (2005)
This research describes an empirical study on Malaysian Internet users. Purposive sampling will be used on adult Malaysian consumers and they are to choose answers with regards to their attitude and perception toward personalization.